Radiographic prevalence of juvenile osteochondral conditions of the proximal interphalangeal joint of Australian Thoroughbred racehorse yearlings and associations with sales results and race performance - Faulkner, Josephine; Vanderperren, Katrien; Duchateau, Luc; O'Sullivan, Chris (Frontiers in Veterinary Science, 2022)
Objectives: Ascertain the radiographic prevalence and variation in characteristics of juvenile osteochondral conditions (JOC) in the proximal interphalangeal joint (PIPJ) of Australian Thoroughbred racehorse yearlings. Establish whether there are any significant associations with public auction sale results and racing performance. Methods: Retrospective evaluation of 1098 yearling repository radiograph sets. Comparison of sales results and whole career racing performance of the case group with two control groups: maternal siblings (N = 397) and yearlings without PIP JOC (N = 391). Results: 6.3% of yearlings had at least one PIPJ JOC lesion with 4.8% having subchondral lucencies of the proximal phalanx (P1SC), 0.6% with subchondral lucencies of the middle phalanx (P2SC) and 0.8% with osteochondral fragmentation (OCF). P1SC were more prevalent in forelimbs and P2SC and OCF were more commonly located in the hindlimbs. 51% of PIPJ JOC were not identified on a lateromedial projection (LM). A significantly lower proportion of horses with OCF were successfully sold at public auction (p  0.05) but there was no significant difference in sales price between the case group and controls. A lower proportion of horses with PIPJ JOC made it to the racetrack to race, although this was not statistically significant. There was no significant difference in racing performance between the case group and controls, although there was a trend towards case horses earning lower career prize money and lower prize money per race (p  0.1). Lesions located in a dorsal or palmar/plantar location on the LM projection earned a lower average prize money per race (p  0.05) than those in a central location, and showed a trend towards earning lower total prize money (p  0.1) and number of places (p  0.1). There was no significant difference in performance for horses with lesions at the medial, axial or lateral aspects of the articular surface. Clinical importance: Overall, the findings of this study indicate that the presence of PIPJ JOC in radiographs of Thoroughbred yearlings should be attributed a low to moderate risk to future racing performance, however certain lesion characteristics may be associated with decreased performance.